Audit on waiting time in a teaching primary care centre - Abd Latip, Nurul Akmal; Mazlan, Mazilah; Roslan, Siti Ruziana; Mohamad Noor, Maizatul Shamimey; Abd Rahman, Mohd Aizuddin; Kamaruzaman, Nor Azam (2021)
Waiting time is one of the factors that could affect a patient’s satisfaction. A study in the Ministry of Health (MOH) primary care clinic showed the average waiting time from registration to consultation was 41 minutes. In IIUM Family Health Clinic (FHC), we adopt MOH client charter for waiting time. The MOH waiting time for registration, consultation and pharmacy should be less than 15 minutes, 30 minutes and 15 minutes respectively. However, there is no consensus on ideal consultation length. This audit aims to identify patient’s waiting time and consultation length in IIUM FHC in order to formulate our own client charter.